Care and Technology Collaboration for Health: Upgrading Prevention of Chronic Complications through Family Empowerment (CATCH-UP) - Widyandari, Ni Made Ayu Sukma; Udayani, Ni Wayan; Wardana, Ida Ayu Fla Aganta; Sa'diyah, Isty Nur Khalimatus (Babali Nursing Research, 2025)
Introduction: Chronic diseases such as chronic kidney disease (CKD), diabetes mellitus, and hypertension are major contributors to morbidity and mortality worldwide, particularly in Indonesia, where they impose significant healthcare burdens. Suboptimal patient self-care, often due to limited digital literacy and inadequate family support, exacerbates disease progression and complications. This study aimed to evaluate the effectiveness of a family-centered, technology-assisted empowerment program in improving digital health literacy, self-care behaviors, and family empowerment among CKD patients undergoing hemodialysis. Methods: A quasi-experimental design involving 60 families allocated into intervention and control groups was employed. Data were collected at two time points—baseline and after the 4-week intervention—using standardized questionnaires for digital literacy (eHEALS), self-care behaviors (SDSCA-CKD), and family empowerment (FES). Baseline data were collected during an initial face-to-face enrollment session, while post-intervention data were collected using secure digital forms. Statistical analyses included paired and independent t-tests and Pearson correlation. Results: The intervention group showed significant improvements in digital health literacy (mean increase = 8.21; p < 0.001), self-care behaviors (mean increase = 16.65; p < 0.001), and family empowerment (mean increase = 1.79; p < 0.001), with strong positive correlations between between family empowerment and self-care (r = 0.257; p = 0.047) and between digital literacy and family empowerment (r = 0.455; p < 0.001). Conclusion: The CATCH-UP model is an effective approach to enhancing self-care and preventing complications in chronic disease management through empowered family engagement and digital literacy enhancement.